ANALYSIS OF MSMEs BUSINESS PERFORMANCE BASED ON INTELLECTUAL CAPITAL AND SOCIAL CAPITAL: Case Study on MSMEs in Gorontalo City - Hafid, Radia; Hafid, Fadila; Dai, Sri Indriyani S; Santoso, Ivan Rahmat; Saleh, Sri Endang (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the performance of MSMEs businesses in Gorontalo city in terms of financial performance and non-financial performance and to determine the influence of intellectual capital directly and indirectly on the performance of MSMEs businesses in Gorontalo City. The approach in this study is quantitative with a correlational method. Data collection in this study was carried out using a questionnaire. The population in this study was 14,507 people and with the Slovin formula, a sample size of 100 people was obtained. Data analysis in this study was descriptive statistics and SEM-PLS. The results of the study showed that 1) the performance of MSMEs businesses for financial performance indicators is in the less good category with a score of 67.07% and for non-financial performance indicators it has a score of 75.26% which is in the fairly good category; 2) intellectual capital directly has a positive and significant effect on MSMEs social capital; 3) intellectual capital directly has a positive but not significant effect on MSMEs business performance; 4) social capital directly has a positive and significant influence on the performance of MSMEs businesses; 5) intellectual capital through social capital has a positive and significant influence on the performance of MSMEs businesses.